Pelatihan Keseimbangan Emosi Di Masa Pandemi Covid-19 (SMPN 88 Jakarta Barat) - Ratu Laura M.B.P; Ratu Nadya W; Windhi Tia Saputra (Universitas Persada Indonesia YAI, 2023)
The world has changed a lot since 2020. Covid-19, whose presence was unexpected, has become afrightening pandemic and has changed the world to this day. The number of changes that occur certainly hasa lot to do with mental health. There are articles reporting signs of depression, anxiety, PTSD and otherpsychological illnesses in the global community during the Covid-19 pandemic. Entering the third year of theCovid-19 pandemic, the impact of the pandemic on children and young people's mental health and well-beingis also being felt and continues to worsen. Disruptions to routines, education, recreation, and anxiety aroundfamily finances and health make many young people feel afraid, angry, and worried about their future. Mentalhealth is related to a person's emotional state. A person's emotional balance plays an important role for thatperson to live well and effectively. This training is aimed at improving emotional balance during the COVID-19 pandemic, especially for the teenage students of SMPN 88 West Jakarta. The selection of training subjectsis considered to be in accordance with the characteristics of the adolescent age which is full of turmoil andemotional instability